Taking stock of Bonhoeffer: studies in biblical interpretation and ethics - Plant, Stephen J. (Ashgate[2014], 2016)
Zusammenfassung: Bonhoeffer's theology continues to prove richly fruitful in the 21st century. This book gathers together Stephen Plant's scholarly engagement with Bonhoeffer's life and theology over two decades. This collection makes accessible distinctive perspective on Bonhoeffer's theology, in particular on the key themes of biblical hermeneutics, ethics, and the intimate connections Bonhoeffer discerns between them